2017
DOI: 10.1016/j.actamat.2017.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and crystallization path of a Fe-based metallic glass alloy

Abstract: The thermal stability and the quantification of the different transformation processes involved in the overall crystallization of the Fe50Cr15Mo14C15B6 amorphous alloy were investigated by several characterization techniques. Formation of various metastable and stable phases during the devitrification process in the sequence α-Fe, χ-Cr6Fe18Mo5, M23(C,B)6, M7C3, η-Fe3Mo3C and FeMo2B2 (with M=Fe, Cr, Mo), was observed by in-situ synchrotron high energy X-ray diffraction and in-situ transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The embrittlement is thus caused by the segregation of phosphorus in separate regions that are less ductile than the matrix and are acting as nucleation sites 58 . However, since the driving force for crystallization during annealing is higher than that for the crystallization upon quenching, the phase separation and nanocrystallization happens quite fast and the sizes of these regions are one to two orders of magnitude larger compared to the nanocrystals formed upon quenching in our case (1 − 1.5 nm) 59 , 60 . Hence, the structural relaxation and phase separation dominates over the ductile FCC crystals formed during quenching, which probably leads to the early failure in the annealed BMGs.…”
Section: Discussionmentioning
confidence: 57%
“…The embrittlement is thus caused by the segregation of phosphorus in separate regions that are less ductile than the matrix and are acting as nucleation sites 58 . However, since the driving force for crystallization during annealing is higher than that for the crystallization upon quenching, the phase separation and nanocrystallization happens quite fast and the sizes of these regions are one to two orders of magnitude larger compared to the nanocrystals formed upon quenching in our case (1 − 1.5 nm) 59 , 60 . Hence, the structural relaxation and phase separation dominates over the ductile FCC crystals formed during quenching, which probably leads to the early failure in the annealed BMGs.…”
Section: Discussionmentioning
confidence: 57%
“…While the foundations of rapid solidification theory for metallic alloys has been established for decades [1][2][3][4][5][6][7][8][9][10], the nucleation and growth phenomena governing the dynamics of phase/morphology selection under the excessive driving forces readily attainable in glass-forming alloys are not so well understood [11,12]. In such cases, the maximization of local-dissipation rates in the regime of sluggish diffusion can give rise to remarkable phases, growth morphologies, and transition sequences [13][14][15][16][17]. Furthermore, non-crystalline atomic ordering in these alloys can fundamentally alter the kinetic response pathways associated with relaxation to crystalline states [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of carbides and borides may be due to the formation of the primary α-Fe phase leading to the segregation and aggregation of C and B elements. M23(CB)6 has a lower enthalpy of formation than other carbides and therefore precipitates preferentially [51]. Previous studies have shown that in amorphous components with high GFA, small atomic sizes C and B have higher crystallization resistance, less prone to diffusion and nucleation [52].…”
Section: Microstructurementioning
confidence: 99%
“…The crystalline product is mainly α-Fe, M23(CB)6 and Fe-C phase. The formation of the M23(CB)6 phase requires the formation of a long-range ordered structure and the migration and aggregation of the transition phase (Fe3B) under the action of high temperatures, resulting in the release of lattice stresses [51]. The released stress promotes the formation of nuclei and inhibits grain growth.…”
Section: Thermal Analysismentioning
confidence: 99%